PENGARUH RASIO KEUANGAN, PERTUMBUHAN PENJUALAN DAN DEVIDEN TERHADAP HARGA SAHAM - Heri Murdianto, 10.05.52.0197; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2014)
This study aims to determine the effect of financial ratios, sales growth and dividends on stock prices on companies manufacturing in Indonesia stock exchange. The population in this study is a manufacturing company that is listed on the Indonesia Stock Exchange 2010-2012. The samples in this study were taken by purposive sampling method. Data were analyzed by using the skewness-kurtosis test for normality, the classical assumption, koofisiendeterminasi test, F-test and test hypotheses. The results in this study are not liquidity effect on stock prices, profitability does not affect the stock price, the sale does not affect the stock price, the dividend policy pisitif significant effect on stock prices, EPS significant positive effect on stock prices. Keywords: stock price, Liquidity, Profitability, Sales, dividend policy, EPS